2014
DOI: 10.7717/peerj.441
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of accommodation and constant resistance training on maximal strength and power in trained athletes

Abstract: Accommodation resistance is a training technique that may improve strength and power gains beyond those achieved by traditional free weights. In this method, chains are either added on a free-weight bar and combined with traditional plates or added to the bar as the entire load.Purpose. The aim of the current study was to compare the effectiveness of accommodation and constant resistance training methods during a four-week period on maximal strength and power in trained athletes.Methods. This study was compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, as previous studies have confirmed the involvement of reactive oxygen species in multiple CVD (Zuo et al, 2011 ; Zhu and Zuo, 2013 ), assessing the potential effects of different diets on the redox balance in the body may be an area of interest for future dietary studies at the molecular level. Further identification of an optimal role of cardiac preconditioning regimens and resistance training may be necessary as these methods may likely modulate lean body mass and muscle strength during WL (Zuo et al, 2013 ; Ataee et al, 2014 ).…”
Section: Perspective and Significancementioning
confidence: 99%
“…Furthermore, as previous studies have confirmed the involvement of reactive oxygen species in multiple CVD (Zuo et al, 2011 ; Zhu and Zuo, 2013 ), assessing the potential effects of different diets on the redox balance in the body may be an area of interest for future dietary studies at the molecular level. Further identification of an optimal role of cardiac preconditioning regimens and resistance training may be necessary as these methods may likely modulate lean body mass and muscle strength during WL (Zuo et al, 2013 ; Ataee et al, 2014 ).…”
Section: Perspective and Significancementioning
confidence: 99%
“…A total of 22 reports that comprised both trained and untrained participants were included for the meta-analysis [ 8 , 16 , 22 , 23 , 24 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. As shown in Figure 2 , VRT and CRT significantly differed in the improvement of the maximum strength of the subjects (ES = 0.80; 95% CI: 0.42–1.19).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis conducted on the studies of only trained subjects showed that VRT favored a significantly higher improvement of maximum strength than CRT (ES = 0.57; 95% CI: 0.22–0.93; Figure 3 ) [ 8 , 22 , 23 , 24 , 32 , 36 , 37 , 38 , 39 ]. Based on the VRT workload, we then subgrouped the studies into <80% and ≥80% 1RM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To participate in this study, 8 Wushu Kung Fu athletes and 8 male fighters were chosen. They were then divided into two groups: the group that used constant resistance and the group that used variable resistance with chains, for a period of four weeks, with three sessions per week (Ataee et al, 2014). During the specific training, all the participants performed 85% of their 1RM training in 3 sets with 5 repetitions and 2 minutes of rest between each series (Bomba & Haff, 2009).…”
Section: Chains and Strengthmentioning
confidence: 99%